ChemInform Abstract: (Imidazol‐2‐yl)methyl‐1, 3‐propanediones: Regioselective C—H Functionalization of the Imidazole Ring by Acylacetylene/Aldehyde Pairs. Issue 27 (16th June 2016) - Trofimov, Boris A.; Andriyankova, Ludmila V.; Nikitina, Lina P.; Belyaeva, Kseniya V.; Mal'kina, Anastasiya G.; Bagryanskaya, Irina Yu.; Afonin, Andrei V.; Ushakov, Igor A.
Abstract: The reaction is carried out under metal‐free conditions with aromatic reactants.